Legal Protection Against Cases of Blasphemy: An Analysis of Legal, Ethical, and Social Impact Aspects In the Context of Freedom Speech - Misdin Arifin HM; Anwar Musaddat (AT-TAFAHUM: Journal of Law, 2019)
The purpose of this study is to analyze the regulation and implementation of Criminal Law regarding the crime of blasphemy. The research method used in this study is a normative research method, namely. legal research, which is carried out to study the laws and regulations that apply to a particular legal problem. The results of this study indicate that Indonesia is a country that recognizes the existence of religion and divinity, therefore the first principle of Pancasila and the preamble to the 1945 Constitution of the Republic of Indonesia expressly state the recognition of divinity in different religions and beliefs. Therefore, everyone must adhere to a certain religious and belief system that is believed to be true. However, every religious community is obliged to maintain harmony between religious communities both in carrying out their religious worship and in implementing the laws they believe in. One of the actions that often causes conflict between religious communities is blasphemy. With the development of information and communication technology (informatics), satire against religion in various virtual media is widely spread both on social media and news media. In order to maintain harmony among religious communities, the government strictly implements the anti-blasphemy law based on various laws and regulations such as the Criminal Code and Law Number 11 of 2016 concerning amendments to Law Number 19 of 2008. Therefore, perpetrators of blasphemy who commit religious acts face the legal consequences of their actions.